Recent Progress on the Molecular Mechanism of Quality Controls Induced by Ribosome Stalling - Ikeuchi, Ken; Izawa, Toshiaki; Inada, Toshifumi (Frontiers in Genetics, 2019)
Accurate gene expression is a prerequisite for all cellular processes. Cells actively promote correct protein folding, which prevents the accumulation of abnormal and nonfunctional proteins. Recent studies demonstrated that ribosome plays crucial roles as a hub for gene regulation and quality controls. Translation elongation is the fundamental step in gene expression to ensure cellular functions, and abnormal translation arrest is recognized and removed by the quality controls. Ribosome-interacting factors are critical for the quality control mechanisms responding to abnormal translation arrest by targeting its products for degradation. Aberrant mRNAs are produced by errors in mRNA maturation steps and cause aberrant translation and are eliminated by the quality control system. In this review, we focus on recent progress on the co-translational quality control mechanisms induced by abnormal translational elongation, which result in the rapid degradation of aberrant polypeptides and mRNAs thereby maintaining protein homeostasis and preventing the protein aggregation.